Global talent management during times of uncertainty - Schlosser, Francine; McPhee, Deborah M. (Bingley, U.K. : Emerald Publishing Limited, 2022)
HRM practitioners and academics have been blindsided by unprecedented changes in the global war on talent. In response, Global Talent Management During Times of Uncertainty offers a multi-disciplinary perspective that identifies emerging global issues and new strategic and research approaches. This volume explores uncertain contexts related to socio-political and socio-economic change. Chapters investigate how rapidly evolving national policies and social and cultural contexts influence the attraction, management, and retention of mobile talent, and consider how such uncertainty may continue to affect post-pandemic global talent management (GTM). Manuscripts in this global volume touch on diverse cultural and geographic contexts, including Canada, the United States, Brazil, Russia, the Ukraine, Norway, Denmark, China, New Zealand, and the United Kingdom. Authors highlight how GTM is influenced by disinformation, cultural differences, and multiple business environments. Scholars identify the importance of cross-disciplinary talent strategies involving military leadership principles when facing uncertainty caused by macro events. GTM practices may not work effectively in a local context but political city initiatives provide avenues for shared regional talent strategies. We delve into perspectives of sustainability, including: the loss of highly skilled workers to more developed countries, the underutilization of skilled immigrants, the retention of post-pandemic healthcare workers, the cultural differences leading to misunderstanding of justice perceptions, and the lasting effects of war and the pandemic on GTM.
Introduction / Francine Schlosser and Deborah M. McPhee -- Part I: Global socio-political change -- Chapter 1. Investigating the role of disinformation on GTM activities / Ali AbdulHussein -- Chapter 2. Reducing uncertainty by contextualising talent / Andrei Kuznetsov and Olga Kuznetsova -- Chapter 3. A guiding framework for leaders in uncertain times: Learning from gtm in the canadian military / Peter A. Voyer -- Chapter 4. Talent management at city level - past experiences and future directions of mobility? / Torben Anderson and Erling Rasmussen -- Part II: Global socio-economic change -- Chapter 5. Being there, done that, known this, and known that: International academic experience and intelligent career competencies / Prantika Ray and Sunil Kumar Maheshwari -- Chapter 6. Global high-tech talent in times of uncertainty / Torben Anderson, Charles M. Vance, and Mitch Rufca -- Chapter 7. Chinese digital talents and monetary rewards: A case study of justice perceptions in a nordic multinational / Linyu Liu and Margit Suurnäkki -- Chapter 8. Preventing brain drain: A sustainable perspective of global talent management / Marcia Carvalho de Azevedo -- Chapter 9. The post-pandemic challenge of retaining, re-attracting, and renewing experienced nursing talent / Francine Schlosser, Deborah M. McPhee, Jody R. Ralph, and Hanna Salminen.
Includes bibliographical references and index.
Keywords: International business enterprises -- Personnel management; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management